Water Erosion in the Donga Soils in Subhumid Zone in West Africa - AVAKOUDJO, JULIEN; KOUELO, Félix Alladassi; Kindomihou, Valentin Missiakô; AKPONIKPE, Pierre Irénikatché; Azontonde, Anastase Hessou; SINSIN, Brice Augustin; AKPLO, Tobi Moriaque; Agonvinon, Mahugnon Socrate (My University, 2020)
The runoff and soil loss were assessed in situ at the scale of 2.12 m 2 plots during the rainy season of 2010 to better understand the determinants and magnitude of the massive soil loss and land subsidence (donga) in the sub-humid zone of Africa in Karimama, North Benin. The experimental de- sign was a split plot with two factors: the topography in 3 modalities (up- stream, center and downstream of the donga) was assigned as main plot fac- tor and the degree of degradation of dongas in 2 modalities (beginner dongas and advanced dongas) was assigned as subplot factor. Runoff water was col- lected through a storage system composed of two tanks. Data were collected on 36 plots (9 plots per donga × 4 dongas). The runoff varies significantly from one site to another for the rainy episode of October 10, 2010. It is twice as high in land use areas (5.87 mm) as in W Park (2.32 mm; l.s.d. = 1.81 mm). From upstream to downstream, runoff and soil loss increased from 2.4 mm to 85.3 mm and 80 g∙m −2 to 197 g∙m −2 , respectively. Runoff is high in the early dongas (7.60 mm) and low in the advanced dongas (5.68 mm) in contrast to lower soil loss in the early dongas (34 g∙m −2 ) and high in the advanced dongas (237 g∙m −2 ). The low value of soil loss with respect to the magnitude of the phenomenon suggests the probable occurrence of other soil loss mechanisms to be elucidated.
Keywords: W National Park; Land Use Areas; Dongas; Runoff; Erosion; Soil Loss